2018
DOI: 10.9734/ijbcrr/2018/43088
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulatory Properties of Powdered Telfairia occidentalis Supplemented Vital Feed Diet on Male Wistar Rats

Abstract: This study was carried out to investigate the immune modulatory properties of different graded stored powdered of Telfairia occidentalis supplemented diet on male wistar rats. Twelve male wistar rats weighing 120g±20g were purchased, acclimatised and randomly allotted into four (T 1 , T 2 , T 3 , T 4) Telfairia occidentalis supplemented groups (0% 5%, 10% and 15%). The rate of their feeding was monitored for three weeks after which the animals were decapitated and the blood and organs were Original Research Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The significantly higher mean corpuscular volume recorded in the E. coli-infected layers in this study on day 14 pi signified a possible macrocytic anaemia. Since the diarrhoea observed in the E. coli-infected birds in this study was not haemorrhagic, it is possible that a deficiency of some vitamins and minerals, such as B 12 , folic acid and cobalt that are essential for normal erythropoiesis may be responsible for the macrocytosis (Ogungbemi et al, 2017). This may be due to reduced feed intake and possible impairment of intestinal absorption as a result of diarrhoea.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The significantly higher mean corpuscular volume recorded in the E. coli-infected layers in this study on day 14 pi signified a possible macrocytic anaemia. Since the diarrhoea observed in the E. coli-infected birds in this study was not haemorrhagic, it is possible that a deficiency of some vitamins and minerals, such as B 12 , folic acid and cobalt that are essential for normal erythropoiesis may be responsible for the macrocytosis (Ogungbemi et al, 2017). This may be due to reduced feed intake and possible impairment of intestinal absorption as a result of diarrhoea.…”
Section: Discussionmentioning
confidence: 73%
“…It has been suggested that septicemia produced by E. coli (Christie and Halliday, 1979) could produce haemodilution which is reflected as reduction in the haematological parameters. Also, these observed changes may be due to reduction in supply of nutritional factors necessary for sustenance of normal erythropoiesis (Esievo, 2017;Ogungbemi et al,2017) because of anorexia and diarrhoea (Feldman et al, 2000) observed in the E. coliinfected group. The significantly higher mean corpuscular volume recorded in the E. coli-infected layers in this study on day 14 pi signified a possible macrocytic anaemia.…”
Section: Discussionmentioning
confidence: 99%